Międzynarodowe kryzysy gospodarcze i ich konsekwencje - Wague, Mamadou (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
To rapid economic deterioration in the world economy affected the majority of developing countries by the crisis. It is felt globally by inhibiting investment, limiting access to credit, bankruptcy publishing companies, the increase in unemployment, the destruction of part of the banking sector, the slowdown of international exchange, reducing revenue to the budgets of rich countries, which may lead to a slowdown in the pace of development assistance to developing countries. The concept of economic crisis, it also serves to draw attention to the following fact: the economy depends to a large extent on the possibility of predicting phenomena, which depends to a large extent on the beliefs of people about the state of the economy, and their future. In contrast, the prospect of troubled times or negative expectations may lead to an economic crisis or the speed of its results. According to the researchers the crisis may be different from the previous financial crises for a number of reasons, namely: in the current global economy and lower inflation is better controlled and is an important factor in easing the crisis